2018
DOI: 10.1216/jca-2018-10-2-265
|View full text |Cite
|
Sign up to set email alerts
|

Toric representations of algebras defined by certain nonsimple polyominoes

Abstract: In this paper we give a toric representation of the associated ring of a polyomino which is obtained by removing a convex polyomino from its ambient rectangle.2010 Mathematics Subject Classification. 13C05, 05E40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…. , I s is a zig-zag walk in P. Following [4] and [20], we briefly recall some notations and a technical Lemma. A binomial f = f + − f − in a binomial ideal J in a polynomial ring over a field is called redundant if it can be expressed as a linear combination of binomials in J of lower degree.…”
Section: Figure 10mentioning
confidence: 99%
See 1 more Smart Citation
“…. , I s is a zig-zag walk in P. Following [4] and [20], we briefly recall some notations and a technical Lemma. A binomial f = f + − f − in a binomial ideal J in a polynomial ring over a field is called redundant if it can be expressed as a linear combination of binomials in J of lower degree.…”
Section: Figure 10mentioning
confidence: 99%
“…Nowadays the study is applied to multiply connected polyominoes, which are polyominoes with one or more holes. In [11] and [20], the authors have proved that the polyominoes obtained by removing a convex polyomino from a rectangle in N 2 are prime. In [13] the authors have introduced a very useful tool to provide a characterization of prime polyominoes.…”
Section: Introductionmentioning
confidence: 99%
“…In [6] and [13], the authors prove that simple polyominoes, namely without holes, are prime. In [8] and [14], a family of prime polyominoes obtained by removing a convex polyomino by a given rectangle was showed. In a more recent paper [10], it is demonstrated that if the polyomino  is prime, then it should have no zig-zag walks, and it is conjectured that this is also a sufficient condition for the primality of .…”
Section: Introductionmentioning
confidence: 99%
“…In general, giving a complete characterization of the primality of multiply connected polyomino ideals seems to be not so easy. A family of prime polyominoes obtained by removing a convex polyomino by a given rectangle has been showed in [8] and [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a prime polyomino ideal is a toric ideal. In Section 3, we present a toric ideal associated to a polyomino, generalizing Shikama's definition in [11]. This toric ideal contains the polyomino ideal (see Proposition 3.1).…”
Section: Introductionmentioning
confidence: 99%